2012
DOI: 10.5430/jha.v2n2p9
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to conventional hospitalization for improving lack of access to inpatient beds: a 12-year cross-sectional analysis

Abstract: Background/Objective: When hospitals cannot guarantee available hospital beds for inpatient admission, patients are exposed to prolonged waits, cancellations and diversions that negatively affect their safety and quality of care. The purpose of this study was to evaluate the effect of a multifaceted intervention for eliminating inpatient access delays.Methods: By using multi-time point cross-sectional analysis, data from all hospitalizations from adult patients registered at an 850-bed public, tertiary-care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Larger capacity of primary care to treat ACSCs results in a significant reduction of the hospitalisations of patients with these conditions 41. Daycare clinics and daycare centres, as well as socially appropriate and less expensive forms of medical care, are widely used in different countries as alternatives to hospital services 3 42 43…”
Section: Discussionmentioning
confidence: 99%
“…Larger capacity of primary care to treat ACSCs results in a significant reduction of the hospitalisations of patients with these conditions 41. Daycare clinics and daycare centres, as well as socially appropriate and less expensive forms of medical care, are widely used in different countries as alternatives to hospital services 3 42 43…”
Section: Discussionmentioning
confidence: 99%
“…This management can improve the quality of patient care, particularly postoperative recovery, while reducing length of stay [4]. Shortened hospital stay is basic to modern patient care and also reduces hospital-acquired infections and venous thromboembolism [5].…”
Section: Discussionmentioning
confidence: 99%
“…The causes of the massive use of the urban ED during winter are complex, but respiratory infections are definitely a major factor [22]- [27]. In previous studies, we reported how the implementation of particular interventions such as replacing residents with staff physicians or the opening of an EDSSU for those patients predicted to need a mean of a 3-day hospitalization resulted in shorter lengths of stays in the ED and might help to alleviate crisis from the ED overcrowding [1] [28]- [32]. Recently, we have published our experience with an EDSSU as an effective and safe alternative to standard inpatient hospitalization during winter for COPD exacerbation patients [8].…”
Section: Discussionmentioning
confidence: 99%